Pengaruh Transfer Pricing, Leverage, Ukuran Perusahaan, dan Intensitas Modal terhadap Tax Avoidance - Endah Yuli Astuti Raki; Gita Desyana; Juanda Astarani (Jurnal Literasi Akuntansi, 2025)
Purpose: This study aims to test and determine the effect of transfer pricing, leverage, company size, and capital intensity on tax avoidance. Method: This research method is quantitative using multiple linear regression analysis. The population used is LQ45 companies listed on the Indonesia Stock Exchange in 2020-2024. The sampling method used is purposive sampling with a total of 85 samples. Finding: The results of the study indicate that transfer pricing, leverage, company size, and capital intensity simultaneously (together) have a significant effect on tax avoidance. In addition, partial results also show that company size and capital intensity have a positive effect on tax avoidance. Homever, transfer pricing and leverage do not affect tax avoidance. Novelty: The difference between this study and previous studies is that this study uses a larger sample and the analysis method used is multiple linear analysis.